1993
DOI: 10.1093/jnci/85.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Failure and Dietary Habits in Women With Breast Cancer

Abstract: Dietary intervention might serve as an adjuvant treatment to improve breast cancer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(49 citation statements)
references
References 0 publications
3
43
0
3
Order By: Relevance
“…29 Studies suggest that total fat intake is significantly inversely associated with survival or positively related to treatment failure (defined as recurrence or new cancer of the contralateral breast). [30][31][32][33][34] Some studies suggest an adverse prognostic effect for obesity. 35,36 Although still inconclusive, these findings raise the possibility that the improved survival of Japanese patients may be related in part to their low mean body weight (obesity rate according to the International Obesity Task Force: 3.3% of Japanese women vs 32% of NHW women 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…29 Studies suggest that total fat intake is significantly inversely associated with survival or positively related to treatment failure (defined as recurrence or new cancer of the contralateral breast). [30][31][32][33][34] Some studies suggest an adverse prognostic effect for obesity. 35,36 Although still inconclusive, these findings raise the possibility that the improved survival of Japanese patients may be related in part to their low mean body weight (obesity rate according to the International Obesity Task Force: 3.3% of Japanese women vs 32% of NHW women 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…An empirical case can be made for both dietary and exercise interventions for breast cancer patients, with data suggesting that obesity at diagnosis, increased fat intake, and weight gain during follow-up are related to recurrence and poorer survival (Holm et al, 1993;Saxe, Rock, Wicha, & Schottenfeld, 1999;Willett, 1999;Zhang, Folsom, Sellers, Kushi, & Potter, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A study of treatment failure and dietary patterns in women with ER-positive breast cancers 28 showed that vitamin E intake at the time of diagnosis was a statistically significant prognostic indicator of treatment failure within the first 2 years after diagnosis (OR ϭ 1.19 for each milligram per 10-MJ increase). These last results are in line with our own findings and suggest that the effect of vitamin E on breast cancer might vary with the stage of the disease.…”
Section: Discussionmentioning
confidence: 99%